2017
DOI: 10.1108/jcp-11-2016-0042
|View full text |Cite
|
Sign up to set email alerts
|

Sadism in sexual homicide offenders: identifying distinct groups

Abstract: Purpose The purpose of this paper is to investigate whether it is possible to identify different types of sadistic offenders within a sample of sexual homicide offenders (SHOs). Design/methodology/approach The study addresses this research question through the use of two-step hierarchal cluster analysis and binary logistic regression utilizing a sample of 350 cases of sexual homicide from Canada. Findings Results from cluster analysis show that three groups emerge: a non-sadistic group, a mixed group that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 33 publications
4
28
1
Order By: Relevance
“…It is possible that different combinations would yield different risk estimations and that maybe a specific constellation of adverse childhood experiences exists, similar to the MacDonald's triad of enuresis, arson, and cruelty to animals . There are also additional predictors of sexual homicide that were not included in the adjusted models. Moreover, considering the heterogeneity of sexual murderers , it would be important in the future to investigate the impact of the adverse childhood experiences on the different types of sexual homicide offenders.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that different combinations would yield different risk estimations and that maybe a specific constellation of adverse childhood experiences exists, similar to the MacDonald's triad of enuresis, arson, and cruelty to animals . There are also additional predictors of sexual homicide that were not included in the adjusted models. Moreover, considering the heterogeneity of sexual murderers , it would be important in the future to investigate the impact of the adverse childhood experiences on the different types of sexual homicide offenders.…”
Section: Discussionmentioning
confidence: 99%
“…They found that crime premeditation, use of physical restraints, mutilations and humiliation were typical characteristics of crimes committed by sexual sadists. In their study based on 350 cases of SH, Reale, Beauregard, and Martineau (2017b) identified distinct groups of SHOs based on varying degrees of sadistic behavior. Three subgroups of SHOs emerged including a severe sadistic group, a mixed group, and a non-sadistic group.…”
Section: Sadistic Sexual Homicides and Crime Scene Behaviorsmentioning
confidence: 99%
“…Finally, we observed a difference in the method of killing. Juvenile sadistic SHOs were more likely to use weapons to kill their victims, whereas strangulation/asphyxiation has been identified as the most common method used by adult sadists (35,46,59,60).…”
Section: Sadisticmentioning
confidence: 99%